2018
DOI: 10.1007/s11295-018-1296-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures of divergence and selection in closely related pine taxa

Abstract: Efforts to detect loci under selection in plants have mostly focussed on single species. However, assuming that intraspecific divergence may lead to speciation, comparisons of genetic variation within and among recently diverged taxa can help to locate such genes. In this study, coalescent and outlier detection methods were used to assess nucleotide polymorphism and divergence at 79 nuclear gene fragments (1212 SNPs) in 16 populations (153 individuals) of the closely related, but phenotypically and ecologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 49 publications
9
27
0
Order By: Relevance
“…shared SNPs among the species, as found in comparative transcriptome sequencing (Wachowiak et al, 2015) and candidate gene studies (Wachowiak, Zaborowska, et al, 2018), confirms their close Under multivariate analysis, three major clusters were identified (with similar resolution when including all available SNPs or only a subset of common polymorphic SNPs), which corresponded to P. sylvestris, P. uncinata and P. mugo/ P. uliginosa. The position of the P. uliginosa samples, between P. sylvestris and P. mugo but more proximate to the latter, has been observed in previous studies (Wachowiak, Żukowska, Wójkiewicz, Cavers, & Litkowiec, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…shared SNPs among the species, as found in comparative transcriptome sequencing (Wachowiak et al, 2015) and candidate gene studies (Wachowiak, Zaborowska, et al, 2018), confirms their close Under multivariate analysis, three major clusters were identified (with similar resolution when including all available SNPs or only a subset of common polymorphic SNPs), which corresponded to P. sylvestris, P. uncinata and P. mugo/ P. uliginosa. The position of the P. uliginosa samples, between P. sylvestris and P. mugo but more proximate to the latter, has been observed in previous studies (Wachowiak, Żukowska, Wójkiewicz, Cavers, & Litkowiec, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…Amerindians transplanted cassava, beans, maize, and genipap from the Amazon to southern Brazil as part of a cyclic agroforestry production system [62]. The Southern-Jê were probably responsible for Araucaria forest expansion over grasslands [27,34,35]. Pre-colonial Southern-Jê and Guarani archaeology reveals evidence of agriculture [30,62,63] and pottery production [30,[62][63][64], and both these activities require fire.…”
Section: Plos Onementioning
confidence: 99%
“…Around 3000 years ago, forest expansion over grasslands intensified [32,33], coinciding with the arrival of the Southern-Jê people in southern Brazil [25,26]. Together with climate changes, humans may have acted as a complementary driver of forest expansion due to transportation of seeds [27,28,34,35], and maintained grasslands using fire [32,33,36]. Recent research has shown that human action was essential for these forests to reach their maximum distribution [34,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports showed that natural selection reduces the level of variability of local genomic regions leaving molecular patterns of selection such as increased genetic divergence around adaptive loci (Nielsen et al 2005;Verta and Jones, 2019;Wachowiak et al 2018). We further tested this hypothesis by co-localizing cis-diverging genes to drought-yield QTL marker regions (shown below; also see Ereful et al 2016).…”
Section: Regulatory Divergence Under Non-stress Conditionsmentioning
confidence: 92%